Vocational Automotive Education Students' Perceptions of the Male Grooming Phenomenon - Lutfianisa, Zahra Nabila; Arsi, Antari Ayuning (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The objective of this study is to identify the reasons male students use cosmetic products and to examine the perceptions of students in the Automotive Engineering Education program regarding the phenomenon of male grooming. This research employed a descriptive qualitative method. The study was conducted at the Faculty of Engineering, Universitas Negeri Semarang. The informants were categorized into three groups: male students who engage in male grooming practices, male students who do not, and female students. The study utilizes the concept of gender stereotypes. The findings indicate that several factors motivate male students to engage in male grooming, including family and peer pressure, job requirements, skin problems, the desire to maintain appearance, and the influence of social media advertising. The phenomenon of male grooming generates varied perceptions among students. For male students who practice male grooming, such behavior is considered normal. However, some male students who do not engage in male grooming, as well as female students, perceive it as inappropriate behavior for students in the Faculty of Engineering. The study reveals that gender stereotypes in the Automotive Engineering Education program remain evident and strongly influence perceptions of male grooming.